Revisiting the modifying environment approach - Jack Phelan (Scottish Journal of Residential Child Care)
Theory is a fundamental piece of professional child and youth care practice, and finding useful, life-space applicable theory that addresses the complex issues presented by the young people in child and youth care is a continual challenge. I would like to describe a cognitive behavioural model that has been part of the literature for almost twenty years, but has been relatively inaccessible because it was not originally presented in life-space friendly language. The theoretical model is entitled the Modifying Environment and was created by Jerome Beker and Reuven Feuerstein and first published in 1990 in two child and youth care journals (Beker & Feuerstein, 1990; 1991 ). Jerry Beker is a personal friend and mentor, and this attempt to update his work is not a criticism of his original work. My hope is to enable newer child and youth care practitioners to be exposed to this important model.